Tanggapan Morfologis dan Fisiologis Jagung Varietas Lokal Tambin terhadap Berbagai Pupuk Organik - Muji Rahayu; Djoko Purnomo; Andriyana Setyawati; Edi Purwanto; Amalia Tetrani Sakya; Samanhudi Samanhudi; Ahmad Yunus; Gani Cahyo Handoyo; Retna Bandriyati Arniputri; Satya Primasasta Zulhivan (Agrotechnology Research Journal, 2021)
Food crops of local varieties are solutions to realize national food security. To boost the production of local corn varieties, various organic fertilizer is promising to develop. This research aimed to study the morphological and physiological response of local variety corn Tambin. The research used a completely randomized design (CRD) one factor with seven treatments: various fertilizers. Various fertilizers consist of no organic fertilizer, liquid organic, compost, cow manure, rabbit urine, chicken manure, and goat manure. The results showed that the application of various organic fertilizers did not affect morphological characters of the local variety of corn Tambin. In This study, the application of various organic fertilizers did not affect the morphological character of corn, including the height of the plant, the number of leaves, the diameter of the stem, the length of the leaves, and the angle of Tambin corn leaves. Application of cow manure, compost, chicken manure, and goat manure could increase the leaf area aged 3 WAP (week after planting) by 716.13 - 1086.52 g per plant. In physiological character, the application of various organic fertilizers could not increase the net assimilation rate, relative growth rate, chlorophyll content, and the specific leave weight. The application of all organic fertilizers, except liquid organic fertilizer, increased the dry weight of plants at the time of harvest by 2.97 – 36.81 g.